Kompetensi pedagogik Guru Pendidikan Pancasila dalam melaksanakan penilaian proses dan hasil belajar yang berpusat pada peserta didik di SMA Negeri 1 Kartasura - Ambar, Ambar; Wijianto, Wijianto; Winarno, Winarno (Academy of Social Science and Global Citizenship Journal, 2024)
This research has two main objectives: 1) To assess the pedagogical competence of Pancasila Education teachers in implementing student-centered assessment processes and outcomes at SMA Negeri 1 Kartasura. 2) To analyze the inhibiting factors faced by Pancasila Education teachers in carrying out student-centered assessment processes and outcomes at SMA Negeri 1 Kartasura. This qualitative study sources data from informants (Pancasila Education teachers), observations of the teaching and assessment processes, as well as documents such as teaching materials for grades X and XI. Sampling was conducted using purposive sampling techniques, and data collection was carried out through interviews, observations, and documentation. Data validation utilized data and technique triangulation. Data analysis followed the steps of data reduction, data presentation, and conclusion drawing as per the Miles and Huberman (1984) approach. The results indicate that Pancasila Education teachers possess good pedagogical competence, but there are still deficiencies in the development of assessment instruments. The assessment process is carried out through the stages of formulating objectives, selecting instruments, conducting assessments, managing results, and reporting. Inhibiting factors include difficulties in understanding student characteristics, the high number of extracurricular activities, and time constraints in conducting assessments.